Summary of Evidence on Nutritional Management for Patients Undergoing Chemotherapy - Xin Dan; Ya‐Lin He; Ya‐Lin Tian; Tang‐Lin Chen; Jia‐Yi Yu (Cancer Medicine)
ABSTRACT Objective This paper aims to consolidate the most robust evidence on nutritional strategies for patients undergoing chemotherapy, offering evidence‐based guidance for clinical practice. The review highlights critical evidence gaps in nutritional therapy for advanced gastric cancer (AGC) patients undergoing systemic therapy, integrating findings from both prospective and retrospective studies. Method According to the “6S” evidence resource pyramid model, clinical decision‐making tools, guidelines, expert consensus, and systematic reviews on nutritional management for chemotherapy patients were systematically retrieved from national and international databases. The methodological quality of the selected literature was evaluated using AGREE II for guidelines, the JBI Evidence‐Based Healthcare Center's standards for systematic reviews, and expert consensus developed by evidence‐based practice experts. Results A total of 47 articles were analyzed, consisting of 12 guidelines, 12 expert consensus statements, and 23 systematic reviews. The findings were categorized into five dimensions: interdisciplinary collaboration, nutritional screening and assessment, nutritional requirements, nutritional therapy, and discharge and follow‐up, resulting in the identification of 62 pieces of relevant evidence. Conclusions The study provides comprehensive, evidence‐based recommendations for nutritional management in chemotherapy patients. Application of the evidence should be adapted to specific clinical scenarios, patient conditions, preferences, and expert judgment to ensure both feasibility and relevance in clinical practice. Contributions This review consolidates diverse nutritional management strategies into a unified framework, addressing evidence gaps in AGC under systemic therapy. Integrating prospective and retrospective studies with interdisciplinary insights provides evidence‐based recommendations to enhance patient care through personalized and standardized approaches.